Nyi Pohaci Sang Hyang Sri value in leader perspective of Cipatat Kolot Customary Societies - Bahagia, Bahagia; Hudayana, Bambang; Wibowo, Rimun; Rangkuti, Zulkifli (Harmoni Sosial: Jurnal Pendidikan IPS, 2021)
This research aims to investigate Nyi Pohaci Sang Hyang Asri’s value in Cipatat Kolot societies perspective. The research method uses an ethnographic qualitative approach. This method is implemented because this research is linked to the social community. To gather data was used as an in-depth interview. Sample are selected through purposive technique. The result is probed meticulously through triangulation technique and triangulation sources. The result shows Nyi Pohaci Sang Hyang Asri is a customary society’s faith. However, it becomes tradition and culture because the value of Nyi Pohaci pursues until nowadays generation. It has been embedded in their perspective. They must continue this perspective because it is mandatory from their forefather. While Nyi Pohaci release in proverb as non-material culture fro pursuing behavior in daily life. The other is Nyi Pohaci through traditional proverb which proverb has numerous meaning including they believe humans are in Nyi Pohaci and Nyi Pohaci are in human bodies. All parts of the human body, starting from human bones, human intellect, human flesh, human form, the hair on human bodies, bile in human stomachs, human minds and minds are formed by eating rice as Nyi Pohaci. As a result, the human dislike to ravage nature environment because Sri has been cultivated on the land’s surface. As land and nature are damaged, they have devastated Sri as paddies. It indicates that a human has influenced Nyi Pohaci belief must protect the natural environment. The other is they adjust their behavior not to adopt fully an-organic agriculture. They try to use composting and fertilizer for livestock manure. As a consequence, the soil can be preserved from damaged and combat global warming like climate change.